2006
DOI: 10.1093/ndt/gfl307
|View full text |Cite
|
Sign up to set email alerts
|

Arterial wave reflections and mortality in haemodialysis patients—only relevant in elderly, cardiovascularly compromised?

Abstract: Background. Chronic kidney disease (CKD) patients have a 3-30-fold increased risk of death compared with the general population. This mortality difference is even more pronounced in younger subjects. Two markers of aortic stiffness--aortic pulse wave velocity (PWV) and augmentation index (AIx)--have been prospectively related to all-cause and cardiovascular (CV) mortality in end-stage renal disease (ESRD) populations. The aims of our study were first, to confirm the important deleterious effect of arterial sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 22 publications
4
40
2
3
Order By: Relevance
“…7 In contrast, a study including 92 patients failed to prove that wave reflections is an independent predictor, as during 61 months of follow-up, no significant differences were noted in cumulative survival among quartiles of AIx (log-rank P=0.780). 30 The findings of this study clarify these issues, as we found that 48-hour ambulatory AIx(75) was significantly associated with higher risk of all-cause mortality or cardiovascular outcomes. Arterial stiffness and wave reflections are generally closely correlated with each other in the general population.…”
Section: Discussionsupporting
confidence: 53%
“…7 In contrast, a study including 92 patients failed to prove that wave reflections is an independent predictor, as during 61 months of follow-up, no significant differences were noted in cumulative survival among quartiles of AIx (log-rank P=0.780). 30 The findings of this study clarify these issues, as we found that 48-hour ambulatory AIx(75) was significantly associated with higher risk of all-cause mortality or cardiovascular outcomes. Arterial stiffness and wave reflections are generally closely correlated with each other in the general population.…”
Section: Discussionsupporting
confidence: 53%
“…36 Amelioration in the arterial wave reflection is particularly significant because it has been found to predict all-cause mortality and cardiovascular disease in ESRD. 37,38 Our findings indicate that therapeutic renal denervation may rapidly affect the peripheral vasculature via a significant reduction of arterial stiffness in this patient cohort.…”
Section: Discussionmentioning
confidence: 65%
“…Briet et al showed that the central pulse pressure was an independent predictor of the progression to end-stage renal disease in CKD patients (Briet et al 2011). Furthermore, some prospective studies have investigated the predictive ability of central pressure indices for cardiovascular prognosis in patients with endstage renal disease (London et al 2001;Safar et al 2002;Covic et al 2006) or in renal transplant recipients (Verbeke et al 2011). Most of the studies have validated that the central pulse pressure and augmentation index predict future cardiovascular events more accurately than, or independently of, the brachial pressure (Hashimoto and Ito 2012).…”
Section: Elastic Aorta Stiff Aortamentioning
confidence: 99%